Tamimahquranic Verses in the Hamparan Perak: Revealing Mystical Theology from the Perspective of Qur'an - Rahimah, Mudrika; Drajat, Amroeni (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2025)
This study aims to explore the theological and social meanings of the tamimah practice based on Qur'anic verses in Hamparan Perak, North Sumatra, through the perspective of the Living Qur'an. This tradition has long been an integral part of local Muslim religious life, functioning as a form of supplication and a symbol of spiritual closeness to Allah SWT. The research employs a qualitative descriptive approach using phenomenological and contextual hermeneutic paradigms. Data were collected through in-depth interviews, participant observation, and documentary studies involving religious leaders, Tamimahmakers, and users within the community. The findings reveal that tamimah is not treated as a magical object but as a medium of prayer, tawassul, and tabarruk to strengthen faith and inner peace. The community makes a clear distinction between tamimah syar'i—derived from Qur'anic verses and the Prophet's supplications—and tamimah shirk, which contains mystical or magical elements. The verses commonly used, such as Ayat al-Kursi, Al-Fatihah, Al-Ikhlas, Al-Falaq, and An-Nas, are believed to possess spiritual power based on authentic hadiths and are used within the framework of ruqyah syar'iyyah. Socially, tamimah serves to strengthen communal solidarity, religious identity, and intergenerational transmission of Islamic values within coastal Muslim society. This study concludes that tamimah represents a tangible manifestation of the Living Qur'an, where the sacred text is not only read but also actualized in daily life through social and spiritual practices. The tradition reflects a harmonious synthesis between Islamic orthodoxy and local wisdom, showcasing the enduring religious-cultural resilience of Indonesian Muslims in responding to modern challenges.